Long-term effects of ABCB1 and SXR SNPs on the systemic exposure to cyclosporine in pediatric kidney transplant patients. (October 2013) - Ferraresso, Mariano; Belingheri, Mirco; Turolo, Stefano; Ghio, Luciana; Tirelli, Amedea Silvia; Grillo, Paolo; Lepore, Marta; Edefonti, Alberto
Aim: Cyclosporine is characterized by a wide interindividual variability in its pharmacokinetics. The objective of this study was to evaluate the effects of ABCB1 and SXR SNPs on cyclosporine exposure in a group of kidney transplant patients followed up from childhood to adulthood.Patients & methods: Recipients were genotyped for ABCB1 C1236T, G2677T/A and C3435T, and for SXR RS3842689 and A7635G. Dose-adjusted trough levels and weight-adjusted daily doses were compared among patients according to allelic status by a generalized estimation equation approach that allows longitudinal data analyses.Results: A genotype-dependent effect was found in all ABCB1 genotypes and in one of the SXR SNPs. This effect was particularly evident for the TT genotype of the ABCB1 G2677T/A SNP, the TT genotype of the ABCB1 C3435T SNP and for heterozygotes of the deletion of 6 bp in the promoter region of SXR .Conclusion: The presence of specific ABCB1 and SXR SNPs could significantly affect cyclosporine exposure during a kidney transplant patient's development from childhood to adulthood in a time-dependent fashion. Original submitted 3 May 2013; Revision submitted 25 July 2013